Environmental education positively impacts the perceptions of learners towards bats in schools in a low socio-economic area in South Africa - Veli Monday Mdluli; Alexandra Howard; Emile Bredenhand; Ara Monadjem; Bekithemba Dube; Adrinajoro Rakotoarivelo; Peter John Taylor (PLoS ONE, 2025)
Bats are amongst the most important ecosystem service providers in the world. This is in part due to their diversity as they are the second largest group of mammals with a widespread global distribution. Despite this, most cultures around the world have negative stereotypes towards bats, largely influenced by myths and beliefs stemming from misconceptions about them. In this study, we aimed to assess the impact of environmental education on enhancing awareness and positive perceptions towards bats and their natural ecosystem services by school learners of ages 11–18 years old in QwaQwa, in the eastern Free State Province of South Africa. Our study addressed negative stereotypes about bats through informed and interactive engagement of scientific and public communication in schools with the use of bat awareness classes, posters, a children’s book on bats, and engagement in bat research revolving around bat boxes installed at each school. We used a standardized questionnaire to assess individual attitudes towards bats pre- and post-intervention, targeting for each survey approximately 200 learners from two primary and one secondary schools in QwaQwa. The perceptions of students were divided into six categories namely scientistic, positivistic, behavioral negativistic, emotional negativistic, cognitive negativistic and myth categories. The intervention resulted in a significant change in negative perceptions of students towards bats for all categories, becoming more positive. We also found gender and age to be important influencers of perceptions for some of the categories. Considering the findings, we argued that intervention through environmental education can be a useful tool for changing negative perceptions of learners towards bats in local South African communities.